Colorimetric Assay of Thiamine Hydrochloride in Pharmaceutical Preparations - Ahmad et al. (مجلة بغداد للعلوم)
A simple, rapid, accurate and sensitive spectrophotometric method for the determination of thiaminehydrochloride has been developed. The method is based on the formation of the Schiff’s base between the primary amino group present in thiamine hydrochloride and aldehyde group present in the vanillin reagent to produce a yellow colored complex having maximum absorption at 390 nm. Beer’s law has obeaid over the concentration range of 2-28µg/mL, with molar absorptivity of 0.96x104L/mol.cm. The average recovery which is a measure of accuracy is 100±1.3% and the relative standard deviation (RSD) is less than1.5 .The present method is considered to be simple because it does not need heating, hydrolysis and solvent extraction steps. The ingredients often formulated with thiamine and have been shown not to interfere, and is suitable for the routine determination of thiamine hydrochloride. The proposed method has been successfully applied for the determination of thiamine hydrochloride in pure form and in pharmaceutical preparations.